BvCPD promotes parenchyma cell and vascular bundle development in sugar beet (Beta vulgaris L.) taproot - Guo, Xiaotong; Li, Yue; Li, Ningning; Li, Guolong; Sun, Yaqing; Zhang, Shaoying (Frontiers in Plant Science, 2023)
Constitutive photomorpogenic dwarf (CPD) is a pivotal enzyme gene for brassinolide (BR) synthesis and plays an important role in plant growth, including increasing plant biomass and plant height, elongating cells, and promoting xylem differentiation. However, little is known about the function of the CPD gene in sugar beet. In the current study, we isolated CPD from Beta vulgaris L.(BvCPD), which encodes protein localized in the nucleus, cell membrane, and cell wall. BvCPD was strongly expressed in parenchyma cells and vascular bundles. The transgenic sugar beet overexpressing BvCPD exhibited larger diameter than that of the wild type (WT), which mainly owing to the increased number and size of parenchyma cells, the enlarged lumen and area of vessel in the xylem. Additionally, overexpression of BvCPD increased the synthesis of endogenous BR, causing changes in the content of endogenous auxin (IAA) and gibberellin (GA) and accumulation of cellulose and lignin in cambium 1-4 rings of the taproot. These results suggest that BvCPD can promote the biosynthesis of endogenous BR, improve cell wall components, promote the development of parenchyma cells and vascular bundle, thereby playing an important role in promoting the growth and development of sugar beet taproot.